Effect of Thermal Expansion Mismatch on Thermomechanical Behaviour of Compacted Graphite Iron - Minghua Cao; Konstantinos P. Baxevanakis; Vadim V. Silberschmidt (Micro, 2024)
Compacted graphite iron (CGI) attracts significant attention in the automotive industry thanks to its suitable thermomechanical properties and cost-effectiveness. A primary fracture mechanism at the microscale for CGI involves interfacial damage and debonding between graphite inclusions and its metallic matrix, which can occur under high-temperature service conditions due to a mismatch in the coefficients of thermal expansion between these two phases. Such microscopic interfacial damage can initiate macroscopic fractures in cast-iron components subjected to thermal loading. While this phenomenon was studied in various composites, there remains a lack of detailed information for CGI, especially related to the complex morphology of its graphite inclusions. This study investigates the influence of graphite morphology and type of matrix on the thermomechanical performance of CGI at high temperatures. A set of three-dimensional finite-element models were developed in the form of unit cells with a single graphite inclusion embedded within a cubic domain of the metallic matrix. Elastoplastic behaviour was assumed for both phases in the numerical simulations. The study is focused on the response of the constituents in CGI to pure thermal loading in order to explore the relationship between graphite morphology and fracture mechanisms. The findings aim to enhance understanding of how graphite morphology affects the behaviours of CGI under high-temperature conditions.